2022
DOI: 10.3389/fmicb.2022.903500
|View full text |Cite
|
Sign up to set email alerts
|

Conventional vs. Organic Agriculture–Which One Promotes Better Yields and Microbial Resilience in Rapidly Changing Climates?

Abstract: In recent years, agricultural productivity has been affected dramatically by climate-related events such as drought. On the other hand, agricultural intensification is expected to increase to satisfy the need for increased global food production. Microbes associated with soil and plants produce a range of bioactive natural products that significantly contribute to crop stress tolerance. Therefore, a better understanding of the parallel effects of agricultural management (conventional and organic croplands) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 66 publications
1
12
0
Order By: Relevance
“…Previous studies have demonstrated that organic practices positively affect soil quality by increasing organic matter and carbon levels compared with conventional farming [1][2][3][4][5] and enhance microbial richness and diversity [6,14,15,39]. The tomato farms investigated in this study have different histories and stand ages, as reflected in their soil profiles.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have demonstrated that organic practices positively affect soil quality by increasing organic matter and carbon levels compared with conventional farming [1][2][3][4][5] and enhance microbial richness and diversity [6,14,15,39]. The tomato farms investigated in this study have different histories and stand ages, as reflected in their soil profiles.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, organic farming practices, such as reduced tillage, cover cropping, and intercropping, can improve soil structure and increase soil organic matter content, creating a favorable environment for soil microbes. Therefore, organic farming practices lead to higher microbial biomass and activity, as well as a greater diversity of microbial communities, compared to conventional farms [ 6 , 14 , 15 ], and thus can contribute to a healthy and more sustainable soil ecosystem.…”
Section: Introductionmentioning
confidence: 99%
“…improved soil structure and moisture retention) and enhanced microbial diversity and abundance might have the potential to increase microbial resistance and resilience towards drought [31,32]. However, it is not well understood to which extent organic and conventional cropping systems differ in their capacity to increase microbial resistance and resilience under drought [33].…”
Section: Introductionmentioning
confidence: 99%
“…Inoculation of plants with single or multiple strains of beneficial microbes has been widely used to enhance plant growth traits, especially for crop plants. Depending on the extent to which the inoculants are efficient, the use of microbial inoculants can contribute towards agricultural productivity with less adverse environmental impacts through the reduction or even elimination of chemical and synthetic fertilizers [18, 19]. However, manipulation of plant microbiomes often does not result in the enhancement of plant traits, and the widespread application of this approach is limited by various biological and experimental factors that affect its efficiency [20].…”
Section: Introductionmentioning
confidence: 99%